ANALISIS PENGARUH KEBIJAKAN PEMERINTAH TERHADAP SELF-EFFICACY DAN KEPUTUSAN STRATEGIS PELAKU UMKM DI INDONESIA SERTA DAMPAKNYA PADA KEBERLANGSUNGAN USAHA PADA MASA PANDEMIC COVID-19 - Muh. Syarifuddin (Scientium Management Review, 2023)
The Covid-19 pandemic has had a significant impact on the ability of MSMEs to maintain their operations. Given the research results, as many as 96% of business entertainers claimed to have experienced the adverse consequences of the Coronavirus on their business processes (A total of 1,785 cooperatives and 163,713 miniature private companies in the middle of the road). Going concern is an important idea in traditional bookkeeping, where in disclosing the annual report, it will decide whether the company will continue its activities or not. It is maintained methodically and measurably as a business plan with procedures. This study will discuss and analyze the effect of government policies on self-efficacy and strategic decisions of MSME players in Indonesia and their impact on business continuity during the co-19 pandemic. The data analysis technique in this study is to use Partial Least Square (PLS) which is a Structural Equation Modeling (SEM) equation model in this study researchers used a minimum sample of 225 respondents. The results of this study are government policies, strategic decisions with OODA Loop and Self-efficacy affect business continuity, and self-efficacy is able to mediate between government policies and business continuity and also successfully mediate strategic decisions with OODA Loop on business continuity.